Analysis Of LEFM Parameters And Fatigue Propagation Of Sent Cracked Am6ob Magnesium Specimens - Nur Hossain (Canadian Institute of Mining, Metallurgy and Petroleum, 2010)
Analysis of Linear Elastic Fracture Mechanics (LEFM) parameters via the Virtual Crack Closure Technique (VCCT) has been obtained for SENT specimens of AM6OB magnesium alloy. It is found that the ratio of initial crack length to initial monotonic plastic zone size is one of the critical factors in establishing the limit of using LEFM concepts. If this ratio is below a certain limit (i.e. when crack lengths are small in comparison to the plastic zone size), loss of similitude stress intensity factor range would occur. This ratio, therefore describes the limit below which the use of LEFM would no longer be admissible. In this study, the above limit was established for AM6OB magnesium alloy. In addition, fatigue crack propagation tests were conducted to ascertain the fatigue response of the alloy and determination of the coefficients of Paris model.